La educación como derecho humano para el desarrollo recíproco - Rodrigo Ichikawa Claro Silva; Paulo Roberto Ciola Castro; Ana Claudia Corrêa Zuin Matttos Amaral (Universidade Federal de Rondônia, 2019)
Considering the Brazilian constitutional panorama, framed in the social-democratic conjuncture, the social right to education emerges as a pillar for social construction. However, the failure to comply with this guideline elaborated by the constituent leads the social framework to involution, in the sense that people do not evolve, nor does the sociopolitical scenario. Today, although the command for the implementation of effective educational policies is understandable, it cannot be affirmed by the effectiveness of this idea, given the factual conjuncture that explains the shortcomings of a failed educational system. Therefore, it is necessary to have a glimpse of the right to education as a basic human parameter, or human right, in order to plan the educational bases through solid systems that, pragmatically, structure a collective framework that even impels the formation of the democratic state. Through the deductive method, doctrinal thoughts on the subject are analyzed, culminating the discussion in the understanding that, perceived as a human right, the right to education demands pragmatic realization and, furthermore, does not allow restrictive incursions through state action, which, in the midst of discretion, sometimes unreasonably restricts the empowerment of the human being. Moreover, it was understood that education optimizes both the individual sphere and the democratic state structure itself.